Beverage consumption patterns and energy contribution from beverages per meal type: results from a national dietary survey in Sweden. Issue 18 (8th October 2018) - Scander, Henrik; Monteagudo, Celia; Nilsen, Bente; Tellström, Richard; Yngve, Agneta
Abstract: Objective: Many studies of food intake have been performed and published in Sweden, but to our knowledge no studies have extensively explored the beverage consumption of the Swedish adult population. The present study aimed to describe the beverage consumption and the contribution of beverage energy (including alcohol energy) to total energy intake according to gender, region of living, meal type and day for a Swedish adult population. Design: National dietary survey Riksmaten (2010–2011), collected by the Swedish National Food Agency. Setting: Sweden. Subjects: A total of 1682 participants (57 % women) reported dietary intake data during four consecutive days, specified by portion size, meal, time point, day of the week and venue. Meals were categorized as breakfast, lunch, dinner and 'other'. Result: The beverage reported to be consumed the most was water (ml/d), followed by coffee. Men had a higher consumption of juice, soft drinks, beer, spirits and low-alcohol beer, while the consumption of tea and water was higher for women. For both genders, milk contributed the most to beverage energy intake. Energy percentage from beverages was higher at lunch and dinner during weekends for both genders. Participants from the biggest cities in Sweden had a higher consumption of wine for both genders and tea for men than participants from other regions. Conclusions: A considerable part of total energy intake was contributed by beverages, especially for men. Beverages can contribute to a more enjoyable diet, but at the same time provide energy, sugar and alcohol in amounts that do not promote optimal health.